2000
DOI: 10.1007/pl00000661
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of complex III core protein 1 and complex V β chain in brains from patients with Alzheimer’s disease and Down syndrome

Abstract: Ubiquinol:cytochrome c oxidoreductase (complex III) and ATP synthase (complex V) are important enzymes in the mitochondrial electron transport chain. Defects in mitochondrial respiratory enzymes have been reported for several neurodegenerative diseases. In this study, we applied the proteomic approach to investigate protein levels of complex III core protein and complex V beta chain in brain regions of Alzheimer's disease (AD) and Down syndrome (DS) patients. Complex III core protein 1 was significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 54 publications
(44 reference statements)
3
65
1
1
Order By: Relevance
“…In addition, in Alzheimer's disease or presenile dementia, which is a progressive and degenerative disease that attacks the brain, a deficiency of ATP synthase has been observed in mitochondria (357). A low expression of the ATP synthase ␤ subunit and the cytosolic accumulation of the ␣ subunit are detected in Alzheimer's disease, and the intraneuronal cytosolic accumulation of the ␣ subunit is implicated in the neurodegenerative process (73,208,367). Moreover, the ATP synthase on the cell surface of endothelial cells has been reported to have an important role in the angiogenesis process required for tumor growth (269)(270)(271)422).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in Alzheimer's disease or presenile dementia, which is a progressive and degenerative disease that attacks the brain, a deficiency of ATP synthase has been observed in mitochondria (357). A low expression of the ATP synthase ␤ subunit and the cytosolic accumulation of the ␣ subunit are detected in Alzheimer's disease, and the intraneuronal cytosolic accumulation of the ␣ subunit is implicated in the neurodegenerative process (73,208,367). Moreover, the ATP synthase on the cell surface of endothelial cells has been reported to have an important role in the angiogenesis process required for tumor growth (269)(270)(271)422).…”
Section: Introductionmentioning
confidence: 99%
“…The only protein found to be downregulated was ATP synthase. It has been shown that protein oxidation may lead to protein conformational changes 38 and loss of function 39,40 . Based on this concept, oxidation and successive loss of function of the proteins identified in our study would lead to the disruption of neuronal communication and diminished energy metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…However, for certain proteins, an apparent discrepancy between adult and fetal DS brain was observed. For example, the levels of 14-3-3 gamma protein and of peroxiredoxins I and II were found to be increased in the adult [90,100] and decreased in the fetal brain [85,163]. For other proteins, changes were observed only in the adult or the fetal brain and not in both.…”
Section: Fetal Brainmentioning
confidence: 95%
“…Proteomic analysis of the mitochondrion electron transport enzymes revealed reduced levels for complex I 24 and 75 kDa subunits, complex III core protein 1, and complex V beta chain in the AD and DS brain [163] and for complex I 30 kDa subunit in the fetal DS brain [164]. Deficiencies in the electron transport may contribute to the progression of the pathology and may affect brain development in the fetus.…”
Section: Synaptosomal and Transport Proteinsmentioning
confidence: 99%